2012
DOI: 10.1519/jsc.0b013e31823daebf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Warm-Up Devices and Rest Period Lengths on Batting Velocity and Acceleration of Intercollegiate Baseball Players

Abstract: It is common among competitive baseball players to swing bats while in the batter's box in an attempt to improve their batting performance. Players use bats of different weights during this time, and only a few studies have evaluated the optimal bat weight to increase performance. Previous studies have not investigated the optimal rest period after a warm-up with bats of varying weights. Therefore, we tested the peak bat velocity of 16 National Collegiate Athletic Association Division II intercollegiate baseba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…Given the total amount of time, batters would step up to plate within the possible optimal time zone (∼6 minutes). As previously reported in a study on various warm-up devices (31), the bat velocity enhancement in the current study falls within the time window (4–12 minutes) of when the greatest effect would be elicited if the stimulus is applied in the on-deck period.…”
Section: Practical Applicationssupporting
confidence: 84%
“…Given the total amount of time, batters would step up to plate within the possible optimal time zone (∼6 minutes). As previously reported in a study on various warm-up devices (31), the bat velocity enhancement in the current study falls within the time window (4–12 minutes) of when the greatest effect would be elicited if the stimulus is applied in the on-deck period.…”
Section: Practical Applicationssupporting
confidence: 84%
“…Incidentally, the first trial of this study belonged to 2 min after a warm-up and the subsequent trials (3rd, 4th, and 5th trials) occurred after 3-to 4-min. This suppressed bat speed result was accorded with a recent study of Wilson et al (2012). They showed increased peak bat speed significantly 4 minutes to 8 minutes after five differently-weighted bat warm-ups compared at 1 minute, 2 minutes, 4 minutes, and 8 minutes after warm-ups.…”
Section: The Transient Bat Speed Within Post-warm-up Swingssupporting
confidence: 86%
“…In addition, a transient effect of bat speed immediately after weighted warm-up were detected only at Otsuji et al (2002) and a recent study of Wilson et al (2012). This transient deterioration and improvement of performance decent time after warm-up trials or acute conditionings has been interpreted as the evidence of post-activation potentiation ([PAP]; Sale, 2002Sale, , 2004Robbins, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Wilson et al (53) exhibited similar findings to that of Williams et al (52) among 16 NCAA Division II baseball players. Wilson et al used a SwingProPlus chronograph (Athnetix, Inc., Arcade, New York, NY) to record various measures of bat velocity and acceleration.…”
Section: Discussionsupporting
confidence: 68%
“…Based on their findings, Van Huss et al (50) suggested the use of overweighted implements increases motor unit activation, with Morimoto et al (30) suggesting the use of underweighted implements results in enhanced neuromuscular activity. Wilson et al (53) suggested that Banister Fitness Fatigue Model may sufficiently explain their findings as the greatest increases in batting performance were observed between 4 and 8 minutes. This model proposes that performance is a balance between fitness and fatigue, whereby changes to the former outlast those of the latter following recent contractile activity (23).…”
Section: Discussionmentioning
confidence: 99%